2007
DOI: 10.1089/thy.2006.0204
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Benign Cold Thyroid Nodules: A Randomized Clinical Trial of Percutaneous Laser Ablation Versus Levothyroxine Therapy or Follow-up

Abstract: A single PLA induced significant volume reduction and improvement of local symptoms. PLA was more effective than LT4. Follow-up was associated with nodule growth and progression of local symptoms. PLA should be considered a potential mini-invasive alternative to surgery in symptomatic patients with benign cold thyroid nodules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
102
2
5

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(113 citation statements)
references
References 31 publications
4
102
2
5
Order By: Relevance
“…25,26 By using laser ablation and microwave ablation, the mean VRR of laser ablation and microwave ablation was 44-62% and 46-65% at the 6-month follow-up. 5,20,27,28 In another study, Jeong et al 9 reported the clinical practice of MRFA for benign thyroid nodules in 236 patients and the mean VRR was 84.79% at the 6-month follow-up. Our result was at least equivalent to that of Jeong's with a MRFA system and seemed to be better than that achieved by laser ablation and microwave ablation.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…25,26 By using laser ablation and microwave ablation, the mean VRR of laser ablation and microwave ablation was 44-62% and 46-65% at the 6-month follow-up. 5,20,27,28 In another study, Jeong et al 9 reported the clinical practice of MRFA for benign thyroid nodules in 236 patients and the mean VRR was 84.79% at the 6-month follow-up. Our result was at least equivalent to that of Jeong's with a MRFA system and seemed to be better than that achieved by laser ablation and microwave ablation.…”
Section: Discussionmentioning
confidence: 98%
“…Similarly, in laser ablation and microwave ablation, the incidence of nerve injury was 0-8% and 0-4.3%. [20][21][22]27,31 This difference suggests that more security might be expected if BRFA is used in thyroid nodules. Thyroid function tests of BRFA group were normal after treatment in this study.…”
Section: Discussionmentioning
confidence: 99%
“…The patient is placed in a supine position with neck hyperextended. The procedure is performed under ultrasound system guidance [59][60][61][62][63][64][65][66][67][68][69][70][71][72][73][74]. In most studies, a 21-G needle is inserted into the lesion along its longest axis.…”
Section: La Devices and Proceduresmentioning
confidence: 99%
“…A laser source, a continuous-wave Nd-YAG laser operating at 1.064 lm, is used with an optical beam-splitting device with as many as four separate fibers that can be illuminated separately or concurrently [12]. The total energy applied is usually between 1.200 and 1.800 Joules [57,59,63,67,73], with a continuous output power of 1.5 and 3.5 W [57, 59-61, 64-72, 74].…”
Section: La Devices and Proceduresmentioning
confidence: 99%
“…Of these eight, we sent a request for data to the authors of three studies [17][18][19] as the data in the papers were insufficient to decide how many people failed in either one or both treatment groups. As of the time of The thyroid measurement is reduced but to < 50% palpation based Thyroxine suppression therapy for benign thyroid nodules submission of this paper, the authors had not responded to our requests for the missing data.…”
Section: Quantitative Synthesismentioning
confidence: 99%